Knowledge and awareness on wildlife among primary school students in Bintulu Sarawak - Mohd Top @ Mohd Tah, Marina; Shohaimi, Shamarina; B., Norshidah (Journal of Multidisciplinary Engineering Science and Technology, 2019)
Lack of knowledge and awareness towards its wildlife diversity and importance could cause the demise of its biological treasures. Knowledge on wildlife and its importance should be developed from an early age. It is vital to allow children to be exposed to the natural environment, which can indirectly create awareness on wildlife conservation at a young age. A study was conducted to determine the knowledge and awareness of wildlife among Year 5 primary school students in Bintulu, Sarawak. A total of 638 respondents from 12 primary schools were involved, and their response was recorded through a survey using questionnaires. From the survey's result, most students have knowledge of the definition of wildlife (76%). Students obtained knowledge and information about wildlife mostly from television (79%), teacher (73%) and family (58%), while less knowledge and information about wildlife from natural habitat (0.5%). Demographic factors also seem to contribute to knowledge on wildlife. Wildlife is significant for people in Sarawak due to the highest food consumption (81%) is from wildlife. Most children had their first exposure to wildlife at the zoo (57%) and from television (32%). From the results, this could mean television, teachers, parents and zoo play important roles in developing the knowledge and awareness of wildlife among children. Nevertheless, exposure through environment educational programs and video documentaries must be blended either in school or home. The knowledge and exposure on wildlife should be nurtured since childhood so that awareness about the importance of wildlife can be raised among young generation.